Assessing the Productivity of Old English –læcan - Gema Maíz Villalta (Miscelánea: A Journal of English and American Studies, 2012)
The aim of this paper is to analyse the productivity of the Old English weak verbs suffixed with -læcan. The main sources for this research are the lexical database of Old English Nerthus and The Dictionary of Old English Corpus. The assessment of productivity is based on the distinction between type-frequency (dictionary-based) and token-frequency (corpus-based). This work contributes to a methodology for assessing the productivity of a morphological process in a historical language as well as for dealing with very low indexes of productivity. The conclusion is reached that the type-frequency of -læcan is relatively high, whereas its productivity is considerably low. It may be affirmed then that a type-frequency higher than token-frequency is compatible with a rather unproductive affix. Finally, the analysis evidences that -læcan suffixed verbs are much more frequent in prose and glosses than in poetry.
Keywords: Old English; frequency; productivity; dictionary; corpus